GAMBARAN PASIEN ANAK DENGAN COVID 19 DI RSUD AJI MUHAMMAD PARIKESIT TENGGARONG KALIMANTAN TIMUR TAHUN 2020 - Magdaleni, Agustina Rahayu; Buchori, Muhammad; Wardhana, Ahmad Wisnu; Muhyi, Annisa; Ningrum, Indras Panca Kusuma; Lambe, Grace Maychale (Fakultas Kedokteran, 2024)
COVID-19, caused by the SARS-CoV-2 virus, has become a global pandemic since late 2019. In Indonesia, data shows that 11% of cases occur in children, but information on clinical and radiological features in children in East Kalimantan, especially Kutai Kartanegara Regency, is still limited. This study aims to determine the characteristics, clinical features, chest radiographs, and laboratory findings of pediatric patients with COVID-19 at Aji Muhammad Parikesit Hospital, Tenggarong in 2020. This study used a descriptive observational research method. The study sample was selected using purposive sampling technique with a total of 139 pediatric patients confirmed with COVID-19 from medical records and digital chest radiograph data. The results showed that the age group of 10-18 years was the most confirmed with COVID-19 (54%), females had the highest number of confirmed COVID-19 cases (53.2%), asymptomatic symptom criteria were obtained in 61.2% and mild in 38.3%. Symptoms were dominated by fever, cough, runny nose, and anosmia. The results of chest radiographs were dominated by abnormal findings (59%) and all on bilateral lungs with consolidation. In blood laboratory, ANC, NLR, Leucocyte, and Thrombocyte levels were dominated by the normal category, while ALC and Hemoglobin levels were dominated by the low category. This study describes the clinical manifestations, laboratory findings, and chest radiographs that are generally found in COVID-19 patients.